Implementasi Algoritma RFID Pada Sistem Portal Parkir Otomatis Berbasis IoT Menggunakan Kartu Tanda Mahasiswa Di Universitas Dirgantara Marsekal Suryadarma - Santoso, Imam; Sultoni, Raden Muh (JURNAL TEKNOLOGI INDUSTRI, 2025)
An efficient and secure parking system is essential in campus environments to improve convenience, administrative order, and vehicle security. This study implements an RFID-based algorithm in an IoT-based automatic parking gate system using Student ID Cards (Kartu Tanda Mahasiswa/KTM) as an authentication medium for motorcycle parking areas. The system consists of an RFID reader, ESP32 microcontroller, vehicle detection sensor, and an automated gate connected to a web-based database. When the card is tapped, the system verifies user data, controls the gate, and records parking data in real time. Test results show that the system achieves high accuracy in card validation and operates with a fast response time. Therefore, this system can enhance order, security, and efficiency in campus parking management and has the potential for further development through mobile application integration.